2018
DOI: 10.1093/jisesa/iey108
|View full text |Cite
|
Sign up to set email alerts
|

Electropenetrography Monitoring of the Neotropical Brown-Stink Bug (Hemiptera: Pentatomidae) on Soybean Pods: An Electrical Penetration Graph-Histology Analysis

Abstract: The Neotropical brown-stink bug Euschistus heros (F.) (Hemiptera: Pentatomidae) is the most important pest damaging soybean in the Neotropics, the world largest production area. The alternating current–direct current (AC–DC) electropenetrography (EPG) technology was used to develop an EPG waveform library of adult females feeding on soybean (Glycine max (L.) Merr.) pods at different input resistor (Ri) levels. Thirteen waveform types/subtypes were identified and described. They were divided into non-probing (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…During T12, all histological analyses showed that the stylet tips were in xylem vessels while visual analyses showed that the stylets remained immobile within the plant tissue. The appearance and electrical origins of this waveform were similar to those of other xylem ingestion waveforms in heteropterans ( Lucini and Panizzi 2017a , 2018a ). According to Mitchell et al (2018) , Lucini and Panizzi (2018a) and Rivera and Mitchell (2020) , insects ingest from xylem for hydration, which may explain the long ingestion periods in xylem vessels.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…During T12, all histological analyses showed that the stylet tips were in xylem vessels while visual analyses showed that the stylets remained immobile within the plant tissue. The appearance and electrical origins of this waveform were similar to those of other xylem ingestion waveforms in heteropterans ( Lucini and Panizzi 2017a , 2018a ). According to Mitchell et al (2018) , Lucini and Panizzi (2018a) and Rivera and Mitchell (2020) , insects ingest from xylem for hydration, which may explain the long ingestion periods in xylem vessels.…”
Section: Discussionsupporting
confidence: 74%
“…Tl3b frequently alternated with Tl3a and was visually correlated with periods when the stylet remained immobile within the plant tissue. Other studies have shown similar stink bug behavior while feeding on vegetative ( Lucini and Panizzi 2017a ) and reproductive structures ( Lucini et al 2016 ; Lucini and Panizzi 2017b , 2018a ). Thus, Tl3a represented the laceration/maceration preparation behaviors, while Tl3b (regular waveform and frequency) were short and represented the ingestion of cell content that was degraded during Tl3a.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Stink bugs feed by inserting their piercing-sucking mouthparts (stylets) into plant tissues (phloem or xylem) either by salivary sheath feeding or by physically rupturing cells (Backus et al, 2005; Lucini and Panizzi, 2018a, b). For salivary sheath feeding on phloem or xylem vessels, stink bugs secrete gelling or SS to form a flange at the site of penetration into the plant and a stabilizing sheath around the stylets (Lucini and Panizzi, 2018b). For both feeding strategies, WS is released to digest cell contents, and the predigested plant material is subsequently ingested.…”
Section: Introductionmentioning
confidence: 99%